2020
DOI: 10.3390/biom10050779
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and Neurochemical Effects of the Putative Cognitive Enhancer (S)-CE-123 on Mesocorticolimbic Dopamine System

Abstract: Treatments for cognitive impairments associated with neuropsychiatric disorders, such as attention deficit hyperactivity disorder or narcolepsy, aim at modulating extracellular dopamine levels in the brain. CE-123 (5-((benzhydrylsulfinyl)methyl) thiazole) is a novel modafinil analog with improved specificity and efficacy for dopamine transporter inhibition that improves cognitive and motivational processes in experimental animals. We studied the neuropharmacological and behavioral effects of the S-enantiomer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…The functional state of DAT has been proven to affect neuronal plasticity and control of cognitive function in the PFC [ 56 , 57 ], where pharmacological inhibition has shown to induce pro-cognitive effects [ 58 ]. DA function in the PFC controls several processes including working memory, attention, flexibility in behavior and action planning [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional state of DAT has been proven to affect neuronal plasticity and control of cognitive function in the PFC [ 56 , 57 ], where pharmacological inhibition has shown to induce pro-cognitive effects [ 58 ]. DA function in the PFC controls several processes including working memory, attention, flexibility in behavior and action planning [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ensemble of behavioral phenotypes observed in DAT−/− rats [ 10 , 11 , 12 , 29 , 30 ] depends primarily on the different roles that DA neurotransmission plays in the mesocortical system and in the PFC [ 58 , 65 ], and it is ascribable to alterations in the cross-talk with glutamatergic neurotransmission [ 23 , 24 , 25 ]. Disruption of these pathways has been widely linked to psychiatric disorders [ 26 ] including autism, schizophrenia [ 27 ] and ADHD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals were assigned randomly to different experimental groups for behavioural, electrophysiological, neurochemical, and molecular evaluation at different time points (1 h, 24 h, or 7 days) after drug discontinuation (Figure 1 ). The experimental group sizes ( n ≥ 5) were chosen based on our previous experimental protocols (Castelli et al, 2014 ; Sagheddu et al, 2020 ; Zanda et al, 2017 ) and are shown in the figure legends. Due to technical issues (e.g., catheter or dialysis probe obstruction), some animals were excluded from statistical analysis, thus reducing the group size in few cases.…”
Section: Methodsmentioning
confidence: 99%
“…( S )-MK-26, synthetized following previously described protocols [ 41 ], has structural similarities to the very well-characterized nootropic modafinil [ 42 ], with the carboxamide replaced with thiazole (five-membered heterocycle attached through position 5) and with a chlorine atom added in the meta position on both phenyl rings, thus also being a close structural analogue of the previously described compounds ( S , S )-CE-158 and ( S )-CE-123 [ 39 , 41 , 42 , 43 ] ( Figure 1 ).…”
Section: Chemistrymentioning
confidence: 98%